2015
DOI: 10.11607/jomi.3787
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Parameters and Levels of Proinflammatory Cytokines in the Crevicular Fluid Around Dental Implants in Patients with Type 2 Diabetes Mellitus

Abstract: The results suggest that dental implant therapy can be offered to patients with well-controlled T2DM, as there were no significant differences between control and diabetic patients in terms of clinical parameters or GCF and PICF cytokine levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 0 publications
0
22
1
Order By: Relevance
“…After full text reading, the 10 studies were excluded due to following reasons: 1) focus on the comparison of PICF interleukin-1 beta (IL-1β) and plasma tumor necrosis factor-alpha (TNF-α) levels between systemically healthy and diabetic subjects [10], 2) directly compare the biomarkers and enzymes of PICF around implants with gingival crevicular fluid (GCF) around natural teeth [11-15], 3) cytokine evaluation with polymerase chain reaction instead of biomarker levels [16-18], 4) sample composed of only failing implants instead of peri-implant diseases [19]. …”
Section: Resultsmentioning
confidence: 99%
“…After full text reading, the 10 studies were excluded due to following reasons: 1) focus on the comparison of PICF interleukin-1 beta (IL-1β) and plasma tumor necrosis factor-alpha (TNF-α) levels between systemically healthy and diabetic subjects [10], 2) directly compare the biomarkers and enzymes of PICF around implants with gingival crevicular fluid (GCF) around natural teeth [11-15], 3) cytokine evaluation with polymerase chain reaction instead of biomarker levels [16-18], 4) sample composed of only failing implants instead of peri-implant diseases [19]. …”
Section: Resultsmentioning
confidence: 99%
“…The role of hyperglycemia in the pathogenesis of peri‐implant diseases has been described by several authors . Animal studies have shown that hyperglycemia has negative effects not only on bone formation but also on bone strength osseointegration and fracture healing .…”
Section: Discussionmentioning
confidence: 99%
“…The role of hyperglycemia in the pathogenesis of peri-implant diseases has been described by several authors. [25][26][27][28][29] Animal studies have shown that hyperglycemia has negative effects not only on bone formation but also on bone strength osseointegration and fracture healing. [30][31][32][33] It has been reported that diabetes (regardless of the degree of glycemic control) represents a contraindication for implant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Once AGEs interact with their specific receptors, proinflammatory cytokines such as interleukin (IL)‐1β and tumor‐necrosis‐factor‐α (TNF‐α) are produced that accumulate in the blood and gingival crevicular fluid (GCF) . These proinflammatory cytokines worsen periodontal inflammation, which may lead to alveolar bone loss around dentition and implants . Long‐term follow‐up studies assessing the survival of adjacent dental implants (ADI) in prediabetic subjects are not yet reported.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] These proinflammatory cytokines worsen periodontal inflammation, which may lead to alveolar bone loss around dentition and implants. 18,19 Long-term follow-up studies assessing the survival of adjacent dental implants (ADI) in prediabetic subjects are not yet reported. We therefore hypothesize that inflammatory parameters (depth of probing [PD], plaque index [PI], and bleedingon-probing [BOP]) and mesial and distal CBL are higher around ADI placed in prediabetic subjects as compared to systemically healthy individuals (controls).…”
Section: Introductionmentioning
confidence: 99%